Antegrade Dissection and Reentry as Part of the Hybrid Chronic Total Occlusion Revascularization Strategy: A Subanalysis of the RECHARGE Registry (Registry of CrossBoss and Hybrid Procedures in France, the Netherlands, Belgium and United Kingdom). (June 2017) - Maeremans, Joren; Dens, Jo; Spratt, James C.; Bagnall, Alan J.; Stuijfzand, Wynand; Nap, Alexander; Agostoni, Pierfrancesco; Wilson, William; Hanratty, Colm G.; Wilson, Simon; Faurie, Benjamin; Avran, Alexandre; et al.
Abstract : Background—: Development of the CrossBoss and Stingray devices for antegrade dissection and reentry (ADR) of chronic total occlusions has improved historically suboptimal outcomes. However, the outcomes, safety, and failure modes of the technique have to be studied in a larger patient cohort. This preplanned substudy of the RECHARGE registry (Registry of CrossBoss and Hybrid Procedures in France, the Netherlands, Belgium and United Kingdom) aims to evaluate the value and use of ADR and determine its future position in contemporary chronic total occlusion intervention. Methods and Results—: Patients were selected if an ADR strategy was applied. Outcomes, safety, and failure modes of the technique were assessed. The ADR technique was used in 23% (n=292/1253) of the RECHARGE registry and was mainly applied for complex lesions (Japanese chronic total occlusion score=2.7±1.1). ADR was the primary strategy in 30% (n=88/292), of which 67% were successful. Bail-out ADR strategies were successful in 63% (n=133/210). The Controlled ADR (ie, combined CrossBoss-Stingray) subtype was applied most frequently (32%; n=93/292) and successfully (81%; n=75/93). Overall per-lesion success rate was 78% (n=229/292), after use of additional bail-out strategies. The inability to reach the distal target zone (n=48/100) or to reenter (n=43/100) most commonly led to failure. ADR-associated major events occurred in 3.4% (n=10/292). Conclusions—: Although mostly applied as a bail-out strategy for complex lesions, the frequency, outcomes, and low complication rate of the ADR technique and its subtypes confirm the benefit and value of the technique in hybrid chronic total occlusion percutaneous coronary intervention, especially when antegrade wiring or retrograde approaches are not feasible. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02075372. Abstract : Supplemental Digital Content is available in the text.